The Effect of Marketing Mix Toward Decisions Become to A Customer BSM Gold Installment Financing Product at Bank Syariah Mandiri Branch Office of Singaparna Tasikmalaya - Lina Marlina; Agus Ahmad Nasrullah; Agung Wahyu Ginanjar (Universitas Pendidikan Indonesia, 2020)
The BSM Gold Installment financing product at Bank Syariah Mandiri continues to experience an increase in the Head Office data. Still, the fact is found in Bank Syariah Mandiri Branch Office SingaparnaTasikmalaya. The number of BSM gold installment financing customers is still low and has not shown a significant increase. The author is interested in analyzing the effect of the marketing mix on becoming a customer of BSM Gold Installment financing products at Bank Syariah Mandiri branch office Singaparna Tasikmalaya. The research method used in this research is quantitative research, and the sample in this study is a saturated sample of 42 respondents. While observation, interviews, and questionnaires do the data collection technique and take data analysis techniques using descriptive data. Hypothesis testing uses correlation analysis test and regression analysis test. The results showed that the marketing mix, namely: products, promotions, places, prices, people, physical evidence, and the process had a significant effect on the decision to become a customer of BSM gold installment financing products at Bank Syariah Mandiri rcount ke rtable with n = 42 at a significance level of 1%, the results for rtable of 0.393 have been obtained. The value of rcount rtable (0.906 0.393) then H0 is rejected.